2017
DOI: 10.3390/w9100746
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Retention by Fly Ash Amended Filter Media in Aged Bioretention Cells

Abstract: Bioretention cells (BRCs) have shown potential for storm water quantity and quality control. However, the phosphorus (P) removal in BRC has been variable due to differences of soil properties in filter media. The objectives of this research were to identify and evaluate P accumulation in filter media and to quantify effluent P reduction in BRC. Each cell has a sand and fly ash media designed to remove phosphorous. Filter media were collected in 2014 across the cell surface and to a depth of 0.6 m to quantify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Previous studies have demonstrated that BCs implemented in relatively small catchments effectively improve both water quantity and quality in response to frequent storm events [9][10][11].In the vegetated filter media, pollutants from storm runoff can be removed through a variety of mechanisms, including physical, chemical and biological processes [12][13][14], and its quality is further enhanced by plant uptake and biological activities in the rhizosphere [15,16]. In recent years, research has shown that BCs can effectively improve water quantity and remove suspended solids [17,18], nutrients [19][20][21], and heavy metals [22,23]. However, it is difficult to meet or maintain a consistently satisfactory performance for reducing nitrogen due to a lack of effective denitrification [24,25].Since it is difficult to achieve consistent high nitrogen removal in standard stormwater bioretention systems, a submerged (anoxic) zone (SZ) combined with a module of BCs added carbon source (C) (e.g., wood chips, shredded newspaper, sawdust etc.)…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that BCs implemented in relatively small catchments effectively improve both water quantity and quality in response to frequent storm events [9][10][11].In the vegetated filter media, pollutants from storm runoff can be removed through a variety of mechanisms, including physical, chemical and biological processes [12][13][14], and its quality is further enhanced by plant uptake and biological activities in the rhizosphere [15,16]. In recent years, research has shown that BCs can effectively improve water quantity and remove suspended solids [17,18], nutrients [19][20][21], and heavy metals [22,23]. However, it is difficult to meet or maintain a consistently satisfactory performance for reducing nitrogen due to a lack of effective denitrification [24,25].Since it is difficult to achieve consistent high nitrogen removal in standard stormwater bioretention systems, a submerged (anoxic) zone (SZ) combined with a module of BCs added carbon source (C) (e.g., wood chips, shredded newspaper, sawdust etc.)…”
mentioning
confidence: 99%
“…On the other hand, FA not only has the capacity to adsorb heavy metals from wastewater, but also has the ability to adsorb other organic/inorganic pollutants from wastewater, including to phosphorous, fluoride, boron, phenolic compounds, pesticides, dyes, etc. [5,151]. Phosphorus is an indispensable element in living organisms.…”
Section: Removal Of Other Organic/inorganic Componentsmentioning
confidence: 99%
“…Many researchers [152,153] have studied the use of FA to remove phosphorus from wastewater. Kandel et al reported that mixture of sand with 5% of FA by weight can effectively reduce phosphorus concentration in water [151]. They showed that the FA has a good effect of adsorb or precipitate phosphate because of the FA contains a certain amount of calcium contents.…”
Section: Removal Of Other Organic/inorganic Componentsmentioning
confidence: 99%
“…For example, Wilson, Riiska, and Albano () found that 29% of chlorothalonil application in a nursery setting was deposited on the ground surface instead of in pots, which led to concentrations up to 500 μg L −1 in runoff, a level toxic to aquatic microorganisms (e.g., 96‐h LC 50 , the concentration that will kill half of a test population, for adult grass shrimp is 150 μg L −1 according to Key, Meyer, & Chung, ). Excess nutrients lead to algal blooms and are an ongoing challenge in both agricultural and urban runoff (Anderson, Gilbert, & Burkholder, ; Kandel, Vogel, Penn, & Brown, ; Paerl et al., ; Smith, ; Smith, King, & Williams, ; Watson et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of frequent irrigation, (e.g., , the concentration that will kill half of a test population, for adult grass shrimp is 150 μg L −1 according to Key, Meyer, & Chung, 2003). Excess nutrients lead to algal blooms and are an ongoing challenge in both agricultural and urban runoff (Anderson, Gilbert, & Burkholder, 2002;Kandel, Vogel, Penn, & Brown, 2017;Paerl et al, 2016;Smith, 2003;Smith, King, & Williams, 2015;Watson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%